Hoping for the Best, Preparing for the Worst: Prepping, sculptural practice and the everyday crisis of insecurity - Day, Jessica Aileen (Curtin University, 2022)
This research project investigates highly individuated preparatory activity, or prepping, through a practice-led research methodology which is articulated through three frameworks identified from commonalities found in prepping’s often highly disparate activities. These frameworks, narrative, adaptable objects, and preservation, aid in sculpturally articulating an often-overlooked aspect of the prepping spectrum. Namely, those attempting to secure already precarious lives in a world of constantly unfolding and speculative crises.